Role of Coping in Stress, Anxiety, Depression among Nursing Students of Purbanchal University in Kathmandu - Samson, Priscilla (Journal of Nepal Health Research Council, 2019)
Background: Unresolved stress among nursing students may occur due to the failure to use effective coping strategies, which may lead to problems such as anxiety and depression.The purpose of this study was to determine the prevalence of stress, anxiety and depression among nursing students and examine its relationship with coping styles. Methods: This descriptive cross-sectional study was conducted among 680 nursing students enrolled in nine colleges affiliated to a university in Nepal during academic year 2018. Depression anxiety stress scale- 21 was used to assess the levels of depression, anxiety and stress. Coping was measured using brief cope inventory. Results: Majority of students (51%, n = 350) reported moderate to extremely severe levels of stress, anxiety, and depression.Students mostly used problem-focused coping strategies. A one-way MANOVA revealed statistically significant differences among the levels of problem- focused coping (Wilks’ Lambda = .96, F (3, 676) = 8.11. p = <.001 and emotion-focused coping (Wilk’s Lambda = .90, F (3,676) = 23.69,p = <.001 with stress, anxiety and depression. Conclusions: The findings can be sourced to create awareness among faculty and administrators of nursing colleges regarding high occurrence of stress, anxiety and depression among students. Future studies can focus on the need to establish the counseling centers in nursing colleges that may aid in teaching students the effective coping strategies.Keywords: Anxiety; brief cope inventory; depression; depression anxiety stress scale;nursing students; stress.